Comparative analysis of foot arch type on explosive power and stability of Kabaddi athlete - Utama, Made Bang Redy; Subekti, Maryoto; Ihsani, Sri Indah; S, Adi; Fastabikulkhoirot, Fastabikulkhoirot (Universitas Tanjungpura, 2025)
Background. Kabaddi is a sport that requires good physical abilities, especially in kabaddi, where the legs are very important for both defensive and offensive players. Variations in the type of foot arch can affect weight distribution, movement efficiency, and postural stability. Objectives. This study aims to analyze the influence of foot arch type (normal arch vs. high arch) on leg muscle explosive power and balance among Kabaddi athletes from Bali